NILAI FILOSOFIS BUDAYA MATRILINEAL DI MINANGKABAU (RELEVANSINYA BAGI PENGEMBANGAN HAK-HAK PEREMPUAN DI INDONESIA) - Iva Ariani (Jurnal Filsafat "WISDOM", 2015)
This research is a qualitative research to find an essence of matrilineal culture in Minangkabau tradition from the philosophical perspective of Feminism. Method of data collection is dividing research areas in West Sumatra into two big groups that are Minang Pesisir and Minang Bukit. Then, collecting data through direct interview and observation to get data about matrilineal system in West Sumatra. Data which has collected then be analyzed using interpretation and hermeneutics method and described as a concept to develop the rights of enforcer process of woman in Indonesia. This research is to develop the woman movements and law concerning femininity in Indonesia that is more suitable with the personality and cultural of Indonesia because it lifted from local and cultural wisdom in Indonesia. The expectation is that it will be able to more suitable to the agenda of offering values of feminist appropriate for public of Indonesia.